Moda sustentável na Amazônia: princípios, processos criativos e produtos eco amigáveis - NAVARRETE, Laura Esmeralda (Universidade Federal do Pará, 2018)
Sustainable fashion, their principles, creative processes, eco-friendly products and theirs new forms of consumption in the Amazon, are the starting point for this research in arts under the ethnocenology approach. From the methodological inducers of the path - project - object - affection of the transdisciplinarity of this ethnoscience, I investigated the course of the brands Da Tribu and Madame Floresta to create a sustainable fashion collection, its inspirations, work philosophy and creation networks. The main theoretical references were Armindo Bião in ethnocenology; Michel Maffesoli in aesthetics and sociology of daily life; in fashion, Renata Pitombo, André Carvalhal and the proposed method of Dijon de Moraes. The research makes a prospect of the near future of sustainable fashion from the present experienced and lived by the Amazon breeders.